Changes in mental health and help-seeking among young Australian adults during the COVID-19 pandemic: a prospective cohort study. Issue 3 (10th February 2023) - Upton, Emily; Clare, Philip J.; Aiken, Alexandra; Boland, Veronica C.; Torres, Clara De; Bruno, Raimondo; Hutchinson, Delyse; Kypri, Kypros; Mattick, Richard; McBride, Nyanda; Peacock, Amy
Abstract: Background: Young people may have elevated risk for poorer mental health during the coronavirus disease 2019 (COVID-19) pandemic, yet longitudinal studies documenting this impact are lacking. This study assessed changes in mental health and help-seeking since COVID-19 restrictions in young Australians, including gender differences. Methods: Data were drawn from a recent subsample ( n = 443; 60% female; M age = 22.0) of a prospective cohort originally recruited in secondary school to complete annual surveys. The subsample completed an additional COVID-19 survey during COVID-19 restrictions (May–June 2020), which was compared to responses from their latest annual survey (August 2019–March 2020). Mixed effect models with time and gender as the primary predictors were conducted for: (i) scores on the Patient Health Questionnaire Depression 9-item (PHQ-9) and Generalised Anxiety Disorder 7-item (GAD-7) modules assessed before and during COVID-19 restrictions, and (ii) self-reported help-seeking from a health professional in February 2020, and the month preceding May–June 2020. Results: Mean symptom scores increased from before to during COVID-19 restrictions on the PHQ-9 (coefficient: 1.29; 95% CI 0.72–1.86) and GAD-7 (0.78; 95% CI 0.26–1.31), but there was no increase in help-seeking over time (odds ratio 0.50; 95% CI 0.19–1.32). There was no evidence of differential changes by gender. Conclusions: This study found increases in depression and anxiety symptoms but not greater help-seeking among young Australian adults during the first wave of the pandemic. Increasing availability and awareness of accessible treatment options and psychoeducation is critical, as well as further research into risk and protective factors to help target treatment to this vulnerable age group.